(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
A Biological factorial experiment was carried out in the field of Al-Qasim Green University , at Agricultural season of 2014/2015. The main objective study Effect of mineral Compound Fertilizer spraying of N.P.K. (0, 1, 1.5 , 2 mml.L-1) with micronutrients (0, 0.50, 0.75, 1 mml.L-1) in some chemical soil properties, Growth and faba bean Vicia faba L (Barcelona class) production. The result showed the positive impact of high level of mineral Compound Fertilizer application N. P. K. application an micronutrients spraying in significantly increases in available nitrogen, phosphorus, potassium, ferrous manganese, zinc and copper in soil, in addition to occur significantly increases in these nutrients in green parts and faba bean with significantly increases in growth and productivity indicters .